Arbitrase dan Litigasi dalam Penyelesaian Sengketa Bisnis di Indonesia - Agil Putri Ramadhani; Izdahara Rizka; Melodi Tiara Pane; Ilham; Yusuf Hidayat; Helfira Citra (CV. ITTC INDONESIA, 2025)
This article analyzes the comparative effectiveness and efficiency of arbitration and litigation in the resolution of business disputes in Indonesia in order to achieve legal certainty. Dispute resolution through litigation offers formal legal certainty and ease of enforcement of court decisions; however, it has several drawbacks, including lengthy procedures, high costs, and open court proceedings that may compromise confidentiality and damage business reputation. In contrast, arbitration provides advantages such as faster and more flexible procedures, confidentiality, and the ability of the parties to appoint arbitrators with expertise relevant to the subject matter of the dispute. The determinant factors influencing the choice of dispute resolution mechanism include time efficiency, cost considerations, information confidentiality, the sustainability of long-term business relationships, and the technical complexity of disputes. Based on these factors, strategies for optimizing arbitration include the inclusion of clear arbitration clauses in contracts, the selection of accredited arbitration institutions such as the Indonesian National Arbitration Board (BANI), the implementation of pre-arbitration negotiations, and the use of e-arbitration with end-to-end encryption systems to ensure confidentiality and effective enforcement of arbitral awards. Therefore, strengthening regulations and enhancing the capacity of national arbitration institutions are essential to support a stable and sustainable investment climate in Indonesia.